Signal Measurement and Prediction of WiMAX Basestations on Taiwan High Speed Rail - Wu, Dan-Chen; Ho, Ping-Fan; Chen, Jyh-Cheng; Yang, Jen-Shun; Chang, Hsien-Wen (My University, 2016)
When communicating at high-speed environment such as high-speed rail, the signals may encounter fast fading due to the terrain changes. In such communication environment, signal prediction can help improve the system throughput and reduce packet loss. In this paper, we propose a prediction mechanism called Window Weight Moving Average (WWMA) to predict the signal strength. We also analyze the real WiMAX signal data collected from Taiwan High Speed Rail (THSR). The analytical results will facilitate the migration from WiMAX to LTE.